In the article are historical of confession of public prosecutor the subject of criminal production - Ротнова, Ірина Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
A thus, analysing historical experience, we see that a requirement is in such public organ, as an office ofpublic prosecutor, with peculiar only to him by the aggregate of tasks, functions and plenary powers, becomes especially sharp in periods of serious transformations in public relations, political system. The organs of office of public prosecutor were always examined and used in quality effective instrument of strengthening of the mode of legality which stipulates development of the legal state. The office of public prosecutor of Ukraine passed the difficult historical way of development, evolved from an organ which protected interests of monarch, to the guarantor of providing of rights and freedoms of man and citizen.